AK247, AK249, AK250, AK280 and AK281 antibodies label mouse glucagon-secreting alpha cells by immunohistochemistry - Guilhen, Cyril; Da Fonte, Sara; Chammartin, Nylsa; Lazzarotto, Célia; Vaudano, Alexandre P.; Gozlugol, Ezgi; Nemeth, Anthony; Payot, Nina; Khatibi, Khatiba; Sassi, Ali; Ollivier, Julien; El Matribi, Zacharie; et al. (Antibody Reports, 2021)
The recombinant antibodies AK247, AK249, AK250, AK280 and AK281 detect by immunohistochemistry the glucagon-secreting alpha cells in mouse pancreatic islets.